Effect of graphene on the performance of nickel foam-based CoNi nanosheet anode catalyzed direct urea-hydrogen peroxide fuel cell. (27th March 2020) - Li, Biaopeng; Song, Congying; yin, Jinling; Yan, Jun; Ye, Ke; Cheng, Kui; zhu, Kai; Cao, Dianxue; Wang, Guiling
Abstract: The highly porous electrode of a crisscrossed CoNi nanosheets array grown on reduced graphene oxide decorated Ni foam (CoNi/rGO@Ni foam) is fabricated through a facile dip and dry method followed by electroreduction and electrodeposition methods. The phase composition and morphology of the electrode are characterized by XRD, SEM, TEM, and EDS. In single electrode tests, CoNi/rGO@Ni foam electrode displays an excellent catalytic performance (330 mA cm −2 at 0.6 V) and stability towards urea electrooxidation when comparing to Ni foam and CoNi nanosheets modified Ni foam (CoNi@Ni foam) electrode. Besides, a low initial oxidation potential of urea electro-oxidation to 0.14 V is achieved on the CoNi/rGO@Ni foam electrode. The introducing of rGO to the electrode greatly reduced the reaction activation energy from 14.47 to 10.35 kJ mol −1 . Besides, large active surface area (261.67 cm 2 ) is also obtained from the electrode. The CoNi/rGO@Ni foam anode exhibits a maximum power density of 12.58 mW cm −2 in direct urea-hydrogen peroxide fuel cell tests. Excellent performance shows in single electrode tests and fuel cell tests suggest that addition of rGO to the electrode is an easy and feasible method to enhance the performance of the catalyst. Highlights: Highly porous electrode: crisscrossed nanosheets array grows on rGO modified Ni foam. The influence of rGO on the catalytic performance of the electrode was researched. Low initial oxidation potential towards urea electro-oxidation was obtained. Achieved an excellent performance and stability when practical use in DUHPFC.